The legal status of customs representatives under the laws of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this paper was studied the legal status of customs representatives, analyzed the conditions for the inclusion of legal persons in the register of customs representatives, discussed the rights, duties, responsibilities of customs representatives and their employees. Conclusions based on the improvement of the current legislation governing the activities of customs representatives. Key words: customs representative, legal status, customs declaration, customs affairs, customs legislation.